THE EFFECT OF STUDENT TEAM ACHIEVEMENT DIVISION COOPERATIVE LEARNING (STAD CL) IN TEACHING THE READING COMPREHENSION - Syafiq, Ahmad Nur; Rahmawati, Amalia (Universitas Muria Kudus, 2017)
This study aims at investigating the effects of Student Team Achievement Division Cooperative Learning (STAD CL) at eleventh grade students of Senior High School 1 Kudus and finding solutions and strategies to make teachers have a formed opinion of the use of STAD in delivering the subject matter while teaching to make more it effective.This study was experimental research. The population of this study was the eleventh year students of Senior High School 1 Kudus in the Academic Year 2015/2016. There were five classes from XI-A to XI -E. Each class had 35 students, so the total population were 175 students. Meanwhile the samples of this study were eighty students from four classes which were selected based on the historical factors and pre-existing ability. 80 students were choosen to be a sample, 40 as experimental group and 40 as control group. Both groups were given the pre-test to measure students' reading skill and after several times of treatments, both groups were given the post-test.The results of the study showed that there was significant difference between the means of experimental and control groups on the reading achievement. Hence, STAD CL was more effective than conventional in the way that mostly students developed their reading performance in the classroom. Further study may also be conducted to determine whether teachers’ use of STAD CL appears to reduce student anxiety and stress in the classroom to improve students’ reading or even other skills, retention, and student-teacher relationships.AbstractPenelitian ini bertujuan